An Overview of Competitive Anxiety and Self-Confidence of Senior Taekwondo Athletes During the Training Phase (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Competitive anxiety is one of the most common psychological factors experienced by athletes and has the potential to influence self-confidence during training and competition. In taekwondo, particularly in the Kyorugi category, excessive anxiety may interfere with concentration, decision-making, and technical execution, ultimately affecting athletic performance. Conversely, high self-confidence can help athletes cope with pressure, maintain focus, and perform optimally. Therefore, understanding the relationship between competitive anxiety and self-confidence during the training phase is essential for effective athlete development. This study aimed to examine the relationship between competitive anxiety and self-confidence and to identify their influence on the performance readiness of senior Taekwondo Kyorugi athletes during the training phase. The study employed a descriptive quantitative approach with a correlational design. Participants consisted of 21 senior Taekwondo Kyorugi athletes aged 19–22 years who were actively involved in training and had competitive experience. Data were collected using a closed-ended questionnaire comprising a 13-item self-confidence scale and the Competitive State Anxiety Test (CSAT) to assess competitive anxiety. Data collection was conducted in a single session and analyzed using correlation analysis with SPSS version 29. The findings revealed a very strong and statistically significant negative relationship between competitive anxiety and self-confidence among senior taekwondo athletes. Athletes with lower anxiety levels tended to demonstrate higher self-confidence, whereas athletes experiencing higher anxiety showed reduced confidence levels. These results indicate that both variables are closely related and play an important role in influencing athletes’ psychological readiness and performance potential. In conclusion, managing competitive anxiety and enhancing self-confidence are essential components of athlete preparation during the training phase. Coaches should integrate psychological training strategies into regular training programs to support optimal athletic performance.